Spontaneous release of interferon gamma by intestinal lamina propria lymphocytes in Crohn's disease. Kinetics of in vitro response to interferon gamma inducers. Issue 4 (April 1991) - Fais, S; Capobianchi, M R; Pallone, F; Di Marco, P; Boirivant, M; Dianzani, F; Torsoli, A
Abstract : The spontaneous induced release of interferon gamma (IFN gamma) by cultured intestinal lamina propria lymphocytes was investigated in patients with Crohn's disease. In contrast to normal lymphocytes, intestinal lymphocytes from these patients spontaneously released IFN gamma and seemed to contain IFN gamma in their cytoplasm. Autologous peripheral lymphocytes did not release IFN gamma. When stimulated with interferon inducers lamina propria lymphocytes from Crohn's disease tissue showed an increase in IFN gamma release 24 hours after induction with no appreciable further increase over the next two days of culture, while in control cells, either peripheral or intestinal, IFN gamma release progressively increased, peaking 72 hours after induction. These findings indicate that in Crohn's disease the intestinal lymphocytes are stimulated in vivo to produce IFN gamma and that the spontaneous IFN gamma production is compartmentalised to the gut lymphocytes. These data support the concept that locally released IFN gamma has a crucial role in cell interactions in the lamina propria and contribute to the locally occurring immune phenomena in Crohn's disease, including the increased epithelial expression of major histocompatibility complex class II antigens.